Population-based stroke incidence estimates in Peru: Exploratory results from the CRONICAS cohort study - Maria Lazo-Porras; Antonio Bernabe-Ortiz; Robert H. Gilman; William Checkley; Liam Smeeth; J. Jaime Miranda (Elsevier, 2022)
Summary: Background: Limited information exists about the incidence of first-ever stroke at the population level, particularly in low- and middle-income countries (LMIC). Longitudinal data from the CRONICAS Cohort Study includes both altitude and urbanization and allows a detailed assessment of stroke incidence in resource constrained settings. The aim of this study was to estimate the incidence and explore risk factors of first-ever stroke at the population level in Peru. Methods: Stroke was defined using a standardised approach based on information from cohort participants or family members. This information was adjudicated centrally by trained physicians using common definitions. Time of follow-up was calculated as the difference between date of enrolment and the reported date of the stroke event. Unstandardised and age-standardised, first-ever stroke incidence rate and 95% confidence intervals (95% CI) were calculated. Generalized linear models, assuming Poisson distribution and link log, were utilized to determine potential factors to develop stroke. Findings: 3,601 individuals were originally enrolled in the cohort and 2,471 provided data for the longitudinal analysis. The median time of follow-up was 7.0 (range: 1 - 9) years, accruing a total of 17,308 person-years. During follow-up, there were 25 incident cases of stroke, resulting in an age-standardised incidence of stroke of 98.8 (95% CI: 63.8-154.0) per 100,000 person-years. After adjustment by age and sex, stroke incidence was higher among people with hypertension (incidence risk ratio (IRR) = 5.18; 95% CI: 1.89 - 14.16), but lower among people living at high altitude (IRR = 0.09; 95% CI: 0.01 - 0.63). Interpretation: Our results indicate a high incidence of first-ever strokes in Peruvian general population. These results are consistent with the estimates found in previous LMIC reports. Our study also found a contributing role of hypertension, increasing the risk of having a first-ever stroke. This work further advances the field of stroke epidemiology by identifying high altitude as a factor related to lower incidence of stroke in a longitudinal study. However, this information needs to be considered with cautions because of the study limitations.